OP24 Effectiveness and safety of ustekinumab 90 mg every 4 weeks in Crohn's disease. (25th January 2019) - Fumery, M; Peyrin-biroulet, L; Nancey, S; Altwegg, R; Veyrard, P; Bouguen, G; Viennot, S; Poullenot, F; Filippi, J; Buisson, A; Bozon, A; Gilletta, C; et al.
Abstract: Background: The most commonly drug regimen for ustekinumab in Crohn's disease (CD) is 90 mg every 8 weeks. Some patients will partially respond to ustekinumab or will experience a secondary loss of response. These patients might benefit from shortening the interval between injections. The efficacy and safety of ustekinumab 90 mg every 4 weeks (90 mg q4W) is unknown. Methods: All patients with active CD, as defined by CDAI > 150 and one objective sign of inflammation (CRP > 5 mg/l and/or faecal calprotectin > 250 μg/g and/or radiologic and/or endoscopic evidence of disease activity) who required ustekinumab dose escalation to 90 mg q4W for loss of response or inadequate response to ustekinumab 90 mg q8W were included in this retrospective multi-centre cohort study. Results: Seventy-six patients, with a median age of 33 years (interquartile range [IQR], 27–42) and median disease duration of 12 years (IQR, 7–16), were included. Optimisation was performed after a median of 4.5 months (IQR, 2.2–7.2) of ustekinumab treatment initiation. Ustekinumab was associated with corticosteroids and immunosuppressants in, respectively, 32% ( n = 25/76) and 32% ( n = 25/76) of cases. Clinical response was observed in 57% ( n = 43/69) after a median of 2.1 months (IQR, 1.0–3.0). After a median follow-up of 8.2 months (IQR, 5.2–12.0), 47% ( n = 36/76) were still treated with ustekinumab, and 26% ( n = 20/76) were in steroid-free clinical remission. Among the 29 patients with colonoscopy during follow-up, 10 had mucosal healing (no ulcers). At the end of follow-up, 35% ( n = 27/76) were hospitalised, and 22% ( n = 17/76) underwent surgery. Adverse events were reported in 9% ( n = 7/76) of patients, including two serious adverse events (pneumonitis, infectious colitis). In multivariate analysis, colonic location (L2) (hazard ratio (HR), 4.6 (95% CI, 1.8–8.4); p = 0.047), inflammatory behaviour (B1) (HR, 9.1 (95CI%, 1.2–16.5); p = 0.015) and duration of ustekinumab therapy before optimisation (HR, 3.2 (95% CI, 1.2–5.4); p = 0.043) were associated with clinical response at 2 months. Conclusions: This is the first study that evaluates the efficacy and safety of ustekinumab optimisation 90 mg q4W in CD. Two-thirds of patients recaptured response following treatment optimisation. Colonic location, inflammatory behaviour, and duration of ustekinumab therapy before optimisation were associated with clinical response at 2 months